Viral meningitis in pregnancy: A case report - Roseingrave, Ruth; Lalchandani, Savita (Clinical Journal of Obstetrics and Gynecology, 2020)
Ms X is a 34 year old para 1 woman who presented at 26+5 weeks’ gestation with fever, neurological symptoms and history of a viral illness. She was treated empirically for bacterial meningitis and transferred to a tertiary maternity hospital. Cerebrospinal fluid (CSF) polymerase chain reaction (PCR) was positive for enteroviral ribonucleic acid (RNA), confirming viral meningitis. Ms X improved clinically and was discharged after six days. A high index of suspicion is required for diagnosis of meningitis in pregnancy. Thorough history, examination and workup is vital for timely treatment. Prognosis in viral meningitis is excellent with no clear adverse fetal or neonatal outcomes.